STUDI TENTANG KAIN PELANGI STUDI KASUS DI INDUSTRI SALSABILLAH COLLECTION PALEMBANG - Maryami, Imranisa; Ernawati, Ernawati; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
Kain Pelangi (Jumputan) is heritage of the ancestor that need to be kept, so the people in Palembang donâ€™t loose their culture. The proplem is, Kain Pelangi in Palembang has no developments. The aim of this research is to describe Kain Pelangi that consist od tools, material that use in the production, motive, motive binding technic and colouring in Kain Pelangi Salsabillah Collection Industri Palembang.The method is decriptive method with qualitative approach. Data collection did by interview, observation and documentation. Then the data studied and analyzed by: data reduction, data presentation, resume taken. The validation did by renew participation, survey determination, triangulation and auditing. The result shows that : 1) the material are cotton, silk, and ATBM silk, Naphtol pigment, Direk, Erionil and pigmen pigment. The tools that is mal, plastic rope, scissors, bailer, flower spray, gloves, plastic glasses and cloth clamp, stove, pot, and mixer spoon, plywoods, and thumbtack. The brush is used to â€œcoletâ€ the pigment. 2) The motive o such as flower motive, geometric motive, diamond and little dot, seven dot, mushrooms, five dot, nine dot, cucung or sumping. 3) motive binding was done and the specification is binding and basting according to the motive pattern. 4) colouring of Kain Pelangi, which are dyeing technic and spraying technic and the last stage using â€œpencoletanâ€ for colouring little motive.